The impact of PrsA over-expression on the Bacillus subtilis transcriptome during fed-batch fermentation of alpha-amylase production - Geissler, Adrian S.; Poulsen, Line D.; Doncheva, Nadezhda T.; Anthon, Christian; Seemann, Stefan E.; González-Tortuero, Enrique; Breüner, Anne; Jensen, Lars J.; Hjort, Carsten; Vinther, Jeppe; Gorodkin, Jan (Frontiers in Microbiology, 2022)
The production of the alpha-amylase (AMY) enzyme in Bacillus subtilis at a high rate leads to the accumulation of unfolded AMY, which causes secretion stress. The over-expression of the PrsA chaperone aids the enzyme folding and reduces stress. To identify affected pathways and potential mechanisms involved in the reduced growth, we analyzed the transcriptomic differences during fed-batch fermentation between a PrsA over-expressing strain and a control in a time-series RNA-seq experiment. We observe transcription in 542 un-annotated regions, of which 234 had significant changes in expression levels between the samples. Moreover, 1,791 protein-coding sequences, 80 non-coding genes, and 20 riboswitches overlapping UTR regions of coding genes had significant changes in expression. Via gene-set over-representation analysis of the differentially expressed genes, we identified putatively regulated biological processes; overall the analysis suggests that the PrsA over-expression affects ATP biosynthesis activity, amino acid metabolism, and cell wall stability. The investigation of the protein interaction network points to a potential impact on cell motility signaling. We discuss the impact of these highlighted mechanisms for reducing secretion stress or detrimental aspects of PrsA over-expression during AMY production.